Meningkatkan Kemampuan Bernalar Kritis Dengan Metode PBL Materi Makna Dan Paham Gereja Fase F SMK Negeri 2 Pematangsiantar - Marta Martina Simanjorang (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Education is a basic, planned effort to create a learning atmosphere and learning process. The Indonesian government is making efforts to improve and develop the education system by renewing the curriculum, improving and developing the teaching system by creating a new curriculum, namely the independent curriculum. In the independent curriculum, Catholic religious education focuses on developing religious understanding, Catholic moral and spiritual values. The independent curriculum emphasizes the Pancasila profile. This research focuses on the critical dimensions of reasoning. This research aims to improve critical reasoning skills, increase students' motivation and learning outcomes on the meaning and understanding of the Church in Phase F Class XI TAV-2 SMK Negeri 2 Pematangsiantar, Catholic Religious Education subjects. This research was conducted in the form of classroom action research. This type of research is quantitative research. This research was conducted in two cycles. The classroom action research cycle consists of planning, implementation, observation, observation and reflection. The method used is problem based learning, which prioritizes solving general problems that commonly occur in everyday life. In this learning model, students are expected to be involved in the research process which requires them to identify problems, collect and use data to solve problems to help increase motivation, critical reasoning skills and learning outcomes of students in Phase F Class XI TAV-2 SMK Negeri 2 Pematangsiantar .